The Foregoing And Delaying eloquent In The poetry of Andalusian Ibn Abd Raboa - عمار ابراهيم البهلول , (Latakia University Journal - Arts and Humanities Sciences Series, 2022)
The research studies purposes of The Foregoing And Delaying Eloquently in the poetry of Andalusian Ibn Abd Rabbou, so this manner – and it's one of many manners of eloquent – does a lot of purposes (such as: The hurry of goodness and badness, make the reader feels the importunes of the foregoing, lust to the delaying if the foregoing pointing on strangeness… etc) This research will deal with these many purposes eloquently for this eloquent type in poetry of Andalusian Ibn Abd Rabbou, Explaining the details by citing poetry for each purpose, that elaborates deeply the eloquent purpose by analyzing study bases on its frame, effection, function, and the denotation value in the poetry esthetic linguist formalizing.